2015
DOI: 10.1167/iovs.15-16852
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Slow Myofibers: The Effect of Sustained BDNF Treatment of Extraocular Muscles in Infant Nonhuman Primates

Abstract: We hypothesize that the oculomotor system adapted to sustained BDNF treatment to preserve normal alignment. Our results suggest that BDNF treatment preferentially altered myofibers expressing slow myosins. This implicates BDNF signaling as influencing the slow twitch properties of EOM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 82 publications
(113 reference statements)
4
32
0
Order By: Relevance
“…53,54 Unilateral oversupply of exogenous BDNF to a horizontal EOM did not induce strabismus in a primate animal model. 55 In our samples, BDNF gene expression was not significantly changed, while both specific receptors for NGF and BDNF, trkA (NTRK1) and trkB (NTRK2), were upregulated in strabismic muscles (Table 2), consistent with our previous microarray report. 21 …”
Section: Discussionsupporting
confidence: 91%
“…53,54 Unilateral oversupply of exogenous BDNF to a horizontal EOM did not induce strabismus in a primate animal model. 55 In our samples, BDNF gene expression was not significantly changed, while both specific receptors for NGF and BDNF, trkA (NTRK1) and trkB (NTRK2), were upregulated in strabismic muscles (Table 2), consistent with our previous microarray report. 21 …”
Section: Discussionsupporting
confidence: 91%
“…We recently showed that both BDNF and tropomyosin receptor kinase B (trkB), the receptor for BDNF, are expressed in adult EOM. 7 This study sought to determine if exogenous treatment with BDNF could alter contraction or relaxation rates in adult rabbit EOM.…”
mentioning
confidence: 99%
“…Recent studies demonstrated that insulin-like growth factor-1 (IGF-1) applied unilaterally over a 3 month time-period to infant monkey medial rectus muscle resulted in development of strabismus, 8 while BDNF treatment did not. 7 However, analysis of the effects of sustained release of BDNF showed that there was a significant effect on the myofibers that expressed the slow myosin heavy chain isoform (MyHC). Not only were these BDNF-treated myofibers significantly larger than age-matched control slow myofibers after the 3 months of continuous BDNF exposure, there was also an increased number of slow-positive myofibers in these BDNF-treated infant extraocular muscles.…”
mentioning
confidence: 99%
See 2 more Smart Citations